Susceptibility of Clostridium botulinum to thirteen antimicrobial agents. - Swenson, J M (1980)
A total of 224 strains of Clostridium botulinum (including isolates from 14 patients with infant botulism and 4 with wound botulism) and 15 strains of C. sporogenes were tested by agar dilution for susceptibility to tetracycline, metronidazole, erythromycin, penicillin, rifampin, chloramphenicol, clindamycin, cephalothin, cefoxitin, vancomycin, sulfamethoxazole-trimethoprim, nalidixic acid, and gentamicin. At least 90% of the C. botulinum strains tested (except for nonproteolytic strains of toxin type F with penicillin) were susceptible to all drugs except sulfamethoxazole-trimethoprim, nalidixic acid, and gentamicin. Minimal inhibitory concentrations for strains from patients with infant and wound botulism were similar to those for other C. botulinum strains.